Prediction of recovery energy from ultimate analysis of waste generation in Depok City, Indonesia - Mega Muitiara Sari; Iva Yenis Septiariva; Eva Nur Fauziah; Kuntum Khoiro Ummatin; Qurrotin Ayunina Maulida Okta Arifianti; Niswatun Faria; Jun-Wei Lim; I Wayan Koko Suryawan (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Refuse derived fuel (RDF) is an environmentally friendly renewable fuel developed to reduce waste generation. RDF can consist of various kinds of waste such as paper and gardens. One of the critical parameters is the chemical element and calorific value. The purpose of this study was to determine the potential for waste reduction and the relationship of ultimate longevity in RDF to the calorific value. This study's paper and garden waste mixture were P0 (100% paper), P25 (75% paper and 25% garden), P50 (50% paper and 50% garden), P75 (25% paper and 75% garden), and P100 (100% garden). The calorific value of the mixture can reach 3.6-5.2 kWh/kg. Simultaneously the relationship of ultimate elements nitrogen (N), hydrogen (H), oxygen (O), and ash affects the heating value of RDF. Sampling the application in Depok City can reduce waste by 6.67%, with the potential for electrical energy from paper and garden wastes of 358,903.8 kWh and 48,681 kWh, respectively. This shows that this energy waste can supply 0.1% of the total daily electricity demand in Depok City.